Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan PT Bintang Matrik Indonesia Kota Bekasi - Aprida Situmorang; Eulin Karlina (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study aims to comprehensively analyze the influence of workload and work environment on employee performance at PT Bintang Matrik Indonesia, Bekasi City, both partially and simultaneously. The background of this research lies in the importance of optimal human resource management to enhance company effectiveness and efficiency. An unbalanced workload can lead to physical and mental fatigue, reducing motivation and productivity, while an unsupportive work environment may decrease employee comfort and job satisfaction. This study uses a quantitative research method with the Slovin sampling technique and data collection through questionnaires distributed to company employees. Data analysis was conducted using classical assumption tests and multiple linear regression to examine the relationships between variables. The results indicate that both partially and simultaneously, workload and work environment have a positive and significant effect on employee performance. Therefore, the company should pay greater attention to workload balance and create a safe, comfortable, and supportive work environment to improve employee performance and loyalty.